Modelling of PM10 concentration in industrialized area in Malaysia : a case study in Nilai and Shah Alam - Tan Cheng Yau (School of Environmental Engineering , University Malaysia Perlis, 2010)
In Malaysia, the predominant air pollutants are suspended particulate matter (SPM) and nitrogen dioxide (NO2). This research is on PM10 as they may trigger harm to human health as well as environment. Six distributions, namely Weibull, log-normal, gamma, Rayleigh, Gumbel and Frechet were chosen to model the PM10 observations at two industrial areas: Nilai and Shah Alam.